2019
DOI: 10.14814/phy2.14023
|View full text |Cite
|
Sign up to set email alerts
|

The role of the nAChR subunits α 5, β 2, and β 4 on synaptic transmission in the mouse superior cervical ganglion

Abstract: Our previous immunoprecipitation analysis of nicotinic acetylcholine receptors ( nAChR s) in the mouse superior cervical ganglion ( SCG ) revealed that approximately 55%, 24%, and 21% of receptors are comprised of α 3 β 4, α 3 β 4 α 5, and α 3 β 4 β 2 subunits, respectively. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 48 publications
(72 reference statements)
4
12
0
Order By: Relevance
“…In β2 KO mice, the SCG neurons express ~75% α3β4 * receptors and ~25% (α3β4) 2 α5 receptors, whereas α5β2 double-KO mice express exclusively α3β4 * hetero-pentameric receptors, making these ideal models for investigating the role of the α5 subunit in endogenous α3β4 * receptors (David et al, 2010 ). Moreover, as discussed below, experiments showed that the percentage of (α3β4) 2 α5 receptors in the plasma membrane is significantly higher than the percentage of the overall receptor pool determined by immunoprecipitation (Simeone et al, 2019 ). With respect to ligand potency, David and colleagues found no difference in either the potency or efficacy of cytisine or DMPP between cultured neurons prepared from either α5β2 double-KO mice or β2 KO mice, and the total number of nACh receptors was not reduced in either α5β2 double-KO mice or β2 KO mice (David et al, 2010 ).…”
Section: The α5 Subunit Co-assembles With α3 and β4 In The Central Anmentioning
confidence: 99%
See 4 more Smart Citations
“…In β2 KO mice, the SCG neurons express ~75% α3β4 * receptors and ~25% (α3β4) 2 α5 receptors, whereas α5β2 double-KO mice express exclusively α3β4 * hetero-pentameric receptors, making these ideal models for investigating the role of the α5 subunit in endogenous α3β4 * receptors (David et al, 2010 ). Moreover, as discussed below, experiments showed that the percentage of (α3β4) 2 α5 receptors in the plasma membrane is significantly higher than the percentage of the overall receptor pool determined by immunoprecipitation (Simeone et al, 2019 ). With respect to ligand potency, David and colleagues found no difference in either the potency or efficacy of cytisine or DMPP between cultured neurons prepared from either α5β2 double-KO mice or β2 KO mice, and the total number of nACh receptors was not reduced in either α5β2 double-KO mice or β2 KO mice (David et al, 2010 ).…”
Section: The α5 Subunit Co-assembles With α3 and β4 In The Central Anmentioning
confidence: 99%
“…These KO mouse models were also used to measure receptor desensitization during prolonged exposure to nicotine in an intact SCG preparation in which compound action potentials (CAPs) were recorded from the postganglionic nerve in response to supramaximal stimulation of the preganglionic nerve. Nicotine added to the superfusion buffer at increasing concentrations yielded IC 50 values of 3.01 μM for α3β4 * receptors and 3.67 μM for (α3β4) 2 α5 receptors (Simeone et al, 2019 ). This small, yet statistically significant difference indicates that the presence of the α5 subunit provides a slight degree of protection from receptor desensitization, although these levels of nicotine are not achieved, even with heavy smoking (Moreyra et al, 1992 ).…”
Section: The α5 Subunit Co-assembles With α3 and β4 In The Central Anmentioning
confidence: 99%
See 3 more Smart Citations